CHILDCARE IN PRIMARY HEALTHCARE: THE NURSE'S ROLE - Viviane Cazetta de Lima Vieira; Claudiane Amaro Fernandes; Marcela de Oliveira Demitto; Luciana Olga Bercini; Maria José Scochi; Sonia Silva Marcon (Universidade Federal do Paraná, 2012)
This study aimed to shed light on aspects related to the role of the nurse in childcare. It is descriptive, exploratory research, of a qualitative nature. Data was provided by all the nurses working in the basic Health Units in Mandaguari-Paraná, was collected in 2010 through semi-structured interviews, and was later submitted to content analysis. Two categories emerged about the theme: childcare and activities it involves, which shows that this is an opportunity to provide guidance on nutrition, immunization and hygiene, and on accompanying the growth of the child, and organization of childcare in the town: between plan and practice, which highlights difficulties of operationalization, such as lack of enablement, absence of protocols, and flaws in the process of reference and counter-reference. The discussions provided an opportunity for reflections about nursing practice in childcare, which can contribute to the development of new strategies for monitoring children's health in the town